A Mixed-Methods Evaluation of the Feasibility of a Medical Management-Based Text Messaging Intervention Combined With Buprenorphine in Primary Care. (March 2022) - Tofighi, Babak; Durr, Meghan; Marini, Christina; Lewis, Crystal F; Lee, Joshua D
Background: Mobile health (mHealth) tools offer an effective and personalized approach to enhance chronic disease management and may partially offset provider-level barriers to increasing buprenorphine prescribing in primary care. This study assessed the feasibility of integrating a text messaging-based medical management tool (TeMeS) in primary care among patients initiating buprenorphine. Methods: TeMeS messages are categorized per the medical management model, programed in a HIPAA-compliant texting software (Apptoto©), and delivered in a tiered fashion over 8-weeks to patients. This mixed-methods evaluation of TeMeS utilized key stakeholder feedback (patients, physicians, administrators, nursing), text messaging software process measures, thematic analysis of patient participant text message content, and electronic administrative data (eg, appointment adherence, treatment retention) at 2-months. Results: The study team approached 65 patients and n = 14 (21%) were ineligible or declined to participate in the study. Most eligible participants owned a smartphone (90%), responded to at least one text query (88%) over an average of 24 days, and few requested to stop receiving texts (6%). Participant text replies included responses to cognitive behavioral therapy-based queries (13.8%), confirming or rescheduling appointments (6.1%), and insurance, pharmacy, or clinical issues pertaining to buprenorphine dispensation or dosing (2%). Suggestions for design modifications included personalizing message content and adjusting message frequency per patient risk of illicit opioid reuse, use of video-based informational content, and real-time provider and staff support for emergent issues. Conclusion: Our findings highlight the acceptability, feasibility, and high rates of engagement of utilizing text messaging to enhance self-management among patients initiating buprenorphine treatment.